2021
DOI: 10.3390/coatings11070774
|View full text |Cite
|
Sign up to set email alerts
|

Topology Optimization of Hard-Coating Thin Plate for Maximizing Modal Loss Factors

Abstract: At present, hard coating structures are widely studied as a new passive damping method. Generally, the hard coating material is completely covered on the surface of the thin-walled structure, but the local coverage cannot only achieve better vibration reduction effect, but also save the material and processing costs. In this paper, a topology optimization method for hard coated composite plates is proposed to maximize the modal loss factors. The finite element dynamic model of hard coating composite plate is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The application of hard coatings in the existing literature mostly focuses on simplifying coated discs [5][6][7][8][9][10][11][12][13][14][15], straight blades [16][17][18][19][20][21], plates [22][23][24][25][26], thin shells [27][28][29][30], and disk drums [31]. Yan et al [5] proposed using virtual layers to simulate changes in coating thickness and analyzed the impact of coating thickness on the natural frequency and forced response of actual disks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of hard coatings in the existing literature mostly focuses on simplifying coated discs [5][6][7][8][9][10][11][12][13][14][15], straight blades [16][17][18][19][20][21], plates [22][23][24][25][26], thin shells [27][28][29][30], and disk drums [31]. Yan et al [5] proposed using virtual layers to simulate changes in coating thickness and analyzed the impact of coating thickness on the natural frequency and forced response of actual disks.…”
Section: Introductionmentioning
confidence: 99%
“…Rouleau et al [21] established a FEM of a blade with a viscoelastic sector, considering the frequency and temperature dependence of viscoelastic materials to study the effects of temperature and rotational speed on damping. Luo et al [22] proposed a method to reduce the amount of damping material used and conducted experiments to verify it. Tassini et al [23,24] indicated that stabilized zirconia (YSZ) coatings have amplitude-dependent mechanical properties and nice damping characteristics.…”
Section: Introductionmentioning
confidence: 99%